Project Planning, Scheduling, and Control the ultimate hands-on guide to bringing projects in on time and on budget - Lewis, James P., 1941- (McGraw-Hill Education, 2023)
The go-to guide for getting projects done on time and on budget--revised and updated with a sophisticated image program and contemporary examples For more than 30 years, James P. Lewis's project management bible has been the benchmark guide for project managers, supervisors, MBA students and everyone studying to pass the PMP® exam. Packed with information on best practices, smart strategies, and a comprehensive survey of the issues you'll encounter as a project manager, it provides an thorough, applications-oriented understanding of the issues in the practice of contemporary project management and a useful reinforcement of the Project Management Institute's recommended success strategies. Every chapter of Project Planning, Scheduling and Control contains a wealth of essential information--from the role of the project manager and description of the PMBOK® Guide to Whole Brain® project management and how to achieve high performance project management. Throughout this edition, you'll find all-new data supporting the information on project definition, planning, execution and control, in chapters that include "Headless-Chicken Projects and How to Prevent Them," "Developing Project Strategy," "Conducting Project Reviews" and more. With an entirely new section offering more strategies on leadership, stakeholder relations, managing a remote team and beyond, and an appendix that includes helpful sections for schedule computations, calculations for an AOA network, and constrained end date scheduling, this latest edition of the classic guide offers the most up-to-date, thorough and hands-on preparation a project manager--or a project manager-in-training--can get.